Identifikasi Senyawa Bioaktif Ekstrak Daun Semak Bunga Putih (Chromolaena odorata) Asal Kota Kupang, Nusa Tenggara Timur - Laut, Meity Marviana; Ndaong, Nemay Anggadewi; Amalo, Filphin Adolfin; Maha, Inggrid Trinidad; Nitbani, Heny; Novian, Dede Rival (JURNAL KAJIAN VETERINER, 2022)
Chromolaena odorata, a member of Asteraceae, is a tropical shrub that grows throughout the year and can dominate pastures. The tropical weed is known as a medicinal plant and has the potential as a natural insecticide. For local people in NTT, the crude extract of the leaves is used to treat myasis on the livestock. C. odorata is also used as silage or food alternative for livestock. This study aims to determine the content of bioactive compounds in C. odorata leaves and determine the extract yield value, as scientific validation of local wisdom in NTT. This research began with the collection of fresh C. odorata leaves, extraction by maceration using 70% ethanol as solvent, solvent evaporation, and phytochemical screening. Phytochemical screening showed that the leaf extract of C. odorata from Kupang City contained high amounts of flavonoids, tannins, alkaloids, triterpenes and steroids and were tested negative for saponins. The extract yield value is 6.09%, means that the extract contains bioactive compunds in high concentration. Further research needs to be done to find out in more detail the content of secondary metabolites from C. odorata leaves and its activity in promote wound healing on livestock in NTT.